High-Voltage Modular Power Supply Using Parallel and Series Configurations of Flyback Converterfor Pulsed Power Applications - Davari, P.; zare, F.; Ghosh, Arindam; Akiyama, H. (Institute of Electrical and Electronics Engineers, 2012)
To cover wide range of pulsed power applications, this paper proposes a modularity concept to improve the performance and flexibility of the pulsed power supply. The proposed scheme utilizes the advantage of parallel and series configurations of flyback modules in obtaining high-voltage levels withfast rise time (dv/dt). Prototypes were implemented using 600-V insulated-gate bipolar transistor (IGBT) switches to generate up to 4-kV output pulses with 1-kHz repetition rate for experimentation.To assess the proposed modular approach for higher number of the modules, prototypes were implemented using 1700-V IGBTs switches, based on ten-series modules, and tested up to 20 kV.Conducted experimental results verified the effectiveness of the proposed method.